Effects of planting configuration and row spacing on growth and production of potato under mulched condition in Dadeldhura, Nepal - Dhakal, Roshan; Joshi, Binod; Bharati, Santosh; Dhakal, Shiva Chandra; Joshi, Khem Raj (Journal of Agriculture and Natural Resources, 2019)
An experiment was conducted at the research site of Dadeldhura, Nepal in 2019 to identify optimum plant spacing for potato under mulched condition. Three levels of inter row spacing; 60 cm with single row per bed (1RB), 45 cm with double row per bed (2RB) and 30 cm with triple row per bed (3RB) and intra row spacing (20, 30 and 40 cm) were laid out in factorial randomized complete block design with three replications. Results showed that there was significant difference (p<0.05) for all parameters except on days to 50% germination, 90% flowering, 50% maturity and on main stem number and graded large sized tuber number and it's weight. Growth parameters namely canopy, leaf number and leaf area were significantly higher (p<0.05) in 60 cm (1RB) ×30 cm spacing. Plant height and leaf area index was significantly higher (p<0.05) in 60 cm (1RB) × 20 cm and 30(3RB) ×20 cm spacing respectively. Total number of tubers m-2 , weight of tubers m-2, weight of marketable tubers m-2, harvest index, number of small sized tuber m-2 ,weight of small sized tubers m-2 and weight of medium sized tubers m-2 were found to be 56.24%,39.79%, 47.98%,4.41%,90.56%, 113.23% and 70.15% significantly higher (p<0.05) in 30 cm (3RB) compared to 60 cm on (1RB) inter row spacing respectively and 59.72%, 61.15%, 58.30%, 4.41%, 114.90%, 137.31%, 55.39% higher in 20cm compared to 40 cm intra row spacing. Interaction effect was significant (p<0.05) in marketable tuber number and medium sized tuber number in which the average highest number of marketable tubers (134.44) and medium sized tubers (121.08) was found in 30(3RB) ×20 cm spacing which was 165.95% and 235.03% significantly higher compared to 60×40 cm spacing respectively. So, this study showed that 30(3RB) ×20 cm spacing would be best spacing combination under mulched condition.